ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PUSKESMAS PEMERINTAH DI KABUPATEN LOMBOK TENGAH - Dyah Sima Puspa Sari; Wahidatul Husnaini; Nurabiah Nurabiah (Bisnis-Net, 2023)
This research was conducted to determine the factors that can affect the performance of accounting information systems. This study aims to empirically examine the effect of user involvement in the system development process, personal engineering capabilities of information systems, information technology sophistication, top management support, and user training and education programs on the performance of accounting information systems at the Central Lombok BLUD Health Center. This research is an associative research with a quantitative approach. This study used primary data obtained through the distribution of questionnaires to respondents, who were employees of puskesmas registered as BLUD in Central Lombok Regency. The sampling technique used was purposive sampling of 70 respondents. The analysis technique used is Structural Equation Modeling- Partial Least Square (SEM-PLS). The results of this study show that user involvement in the system development process, personal engineering capabilities of information systems, top management support and user training and education programs have a significant positive effect on the performance of accounting information systems while the sophistication of information technology has no effect on the performance of accounting information systems